Live Attenuated Influenza Vaccination Before 3 Years of Age and Subsequent Development of Asthma: A 14-year Follow-up Study - Baxter, Roger P. (Pediatr Infect Dis J, 2018)
BACKGROUND: Live-attenuated influenza vaccines (LAIVs) are not licensed in children younger than 2 years of age because of a wheezing safety signal that has not been fully elucidated. In 2000, the Kaiser Permanente Vaccine Study Center conducted a placebo-controlled randomized clinical trial (RCT) of LAIV in children. As many of these children were still enrolled in Kaiser Permanente in 2014, we could assess the possible long-term association between LAIV and subsequent asthma diagnosis. METHODS: We identified all children who were originally enrolled into the LAIV RCT at younger than 3 years of age. We followed up subjects until disenrollment from the health plan, a first diagnosis of asthma, or through the end of the study period in 2014. Asthma was defined by a first International Classification of Diseases, 9th revision, Clinical Modification code (493.*) assigned at an outpatient or emergency department encounter. We performed a survival analysis of time to first asthma diagnosis among children receiving LAIV or placebo with a Cox proportional hazards model. RESULTS: We identified 1151 children in the original RCT who were 12 through 35 months of age at the time of enrollment and who had received 2 doses of LAIV or placebo. A total of 767 (66.7%) RCT participants were still Kaiser Permanente Northern California members in 2014. There was no evidence of differential dropout by treatment group. The hazard ratio for new-onset asthma for LAIV recipients compared with placebo was 1.1 (95% confidence interval: 0.88–1.41; P = 0.38). CONCLUSIONS: We found no evidence of increased risk of subsequent asthma diagnosis among children younger than 3 years of age who received LAIV compared with placebo.